Water column raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO245 - Ferdelman, Timothy G (PANGAEA, 2025)
Water column raw data using the ship's own Kongsberg EM 122 multibeam echosounder was almost continuously recorded during RV SONNE cruise SO245. Data was recorded on 33 days between 2015-12-23 and 2016-01-25 in the South Pacific Ocean (during transit also crossing the flank of the Leont'ev Seamount). These profiles are part of the corresponding raw dataset (https://doi.org/10.1594/PANGAEA.980702) (which include the .all files). The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. This publication is conducted within the efforts of the German Marine Research Alliance in the core area 'Data management and Digitalization' (Deutsche Allianz Meeresforschung, DAM).
Keywords: Bathymetry; Multibeam Echosounder